Treatment of ankle sprain or instability in Korean medicine clinics: A protocol for a prospective multicenter observational study - Gajin Han; Mi Mi Ko; Song-Yi Kim; Ye-Seul Lee (Integrative Medicine Research)
Background: Korean medicine (KM), including acupuncture, has been used to treat many patients with ankle sprains in Korea. The purpose of this prospective observational study is to determine how ankle sprains are treated using KM practice and to assess the outcomes of these treatments. Methods: We will perform a prospective observational study to include around 200 participants from KM clinics with a chief complaint of ankle sprain or ankle instability. All participants will receive individualized KM treatments which may include acupuncture, pharmacopuncture, moxibustion, cupping therapy, and herbal medicine. The participants will be assessed on the information related to both ankle discomfort using a visual analogue scale and on the participant's overall condition including quality of life. Discussion: Through this study, we would be able to collect specific and detailed data for various treatments from actual practice, such as the characteristics of the KM treatment system for treating ankle sprains or the method of acupuncture point selection. We also expect that the results of this study based on daily clinical practice will allow other researchers to create research questions that are beneficial from a clinical, societal, and patient's perspective. Clinical research registration: This study has been registered at the Clinical Research Information Service (CRiS) of Korea: KCT0004016.